Oral Presentations 1981
DOI: 10.1055/s-0038-1652083
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Of Protamine Sulfate With Thrombin

Abstract: Protamine sulfate, a simple protein M.W. 4,600, is a known antiheparin agent which, in the absence of heparin, demonstrates an anticoagulant activity both in vitro and in vivo. Much work has been done to elucidate the interactions of heparin with thrombin and ATIII, however, little is known about the mechanism of protamine sulfate anticoagulant activity and its effect on thrombin.In binding studies, radiolabeled thrombin was reacted with protamine for 1 hour and ATIII was then used as a probe to test the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…A higher protamine to heparin ratio of 3:1 significantly affected the R time in the study by Khan et al 14 . Effects of protamine that may reduce thrombin generation 16,17 include reduction in FV and FVII activation 18 and FVIII activity 19 . However, in our study there was no evidence that protamine added an additional anticoagulant effect, as the R time and K time remained unchanged or in some patients the R time reduced.…”
Section: Discussioncontrasting
confidence: 58%
“…A higher protamine to heparin ratio of 3:1 significantly affected the R time in the study by Khan et al 14 . Effects of protamine that may reduce thrombin generation 16,17 include reduction in FV and FVII activation 18 and FVIII activity 19 . However, in our study there was no evidence that protamine added an additional anticoagulant effect, as the R time and K time remained unchanged or in some patients the R time reduced.…”
Section: Discussioncontrasting
confidence: 58%
“…Several previous studies have demonstrated an anticoagulant effect of protamine [4][5][6][10][11][12] . For example, Mochizuki et al showed that protamine to heparin ratios >1.3:1 in vitro prolong the ACT and reduce ADP-induced platelet aggregation 5 .…”
Section: Protamine Concentration (Mg/ml) R Time (Min)mentioning
confidence: 99%
“…The mechanism involved in the anticoagulant effect of protamine has not been fully elucidated, but appears to involve several processes 10,11 . Protamine is known to precipitate fibrinogen and fibrin monomer 10 , and also reversibly inhibits thrombin, and the inactivation of thrombin by antithrombin III 11 .…”
Section: Protamine Concentration (Mg/ml) R Time (Min)mentioning
confidence: 99%
“…This may be due to direct interactions of protamine with clotting factors, particularly thrombin. 40 In addition to confirming the ability of rPF4 to reverse heparin anticoagulation without apparent adverse side effects, these data highlight another potential limitation of protamine, specifically a narrow therapeutic window.…”
Section: Use Of Rpf4 In Animal and Ex Vivo Human Studiesmentioning
confidence: 62%